Overexpression of DEMETER, a DNA demethylase, promotes early apical bud maturation in poplar. (12th October 2017) - Conde, Daniel; Moreno‐Cortés, Alicia; Dervinis, Christopher; Ramos‐Sánchez, José M.; Kirst, Matias; Perales, Mariano; González‐Melendi, Pablo; Allona, Isabel
Abstract: The transition from active growth to dormancy is critical for the survival of perennial plants. We identified a DEMETER‐like ( CsDML ) cDNA from a winter‐enriched cDNA subtractive library in chestnut ( Castanea sativa Mill . ), an economically and ecologically important species. Next, we characterized this DNA demethylase and its putative ortholog in the more experimentally tractable hybrid poplar ( Populus tremula × alba ), under the signals that trigger bud dormancy in trees. We performed phylogenetic and protein sequence analysis, gene expression profiling, and 5‐methyl‐cytosine methylation immunodetection studies to evaluate the role of CsDML and its homolog in poplar, PtaDML6. Transgenic hybrid poplars overexpressing CsDML were produced and analysed. Short days and cold temperatures induced CsDML and PtaDML6 . Overexpression of CsDML accelerated short‐day‐induced bud formation, specifically from Stages 1 to 0. Buds acquired a red‐brown coloration earlier than wild‐type plants, alongside with the up‐regulation of flavonoid biosynthesis enzymes and accumulation of flavonoids in the shoot apical meristem and bud scales. Our data show that the CsDML gene induces bud formation needed for the survival of the apical meristem under the harsh conditions of winter. Abstract : Winter dormancy is a pivotal developmental and physiological process for the survival of the main terrestrial carbon sink: temperate and boreal forests. These works reveal the crosstalk between the environmentally‐controlled active DNA demethylation and bud maturation in poplar. Indeed, the evidences presented here provide direction for future studies designed to address regulation of shoot growth in response to the environment.